Integrasi Ego State: Konseling Traumatik Menggunakan Ego State Therapy - Habsy, Bakhrudin All; Amalda, Amalda; Hariono, Kanaya Violetta; Yahya, Khairunisha Nabila (TSAQOFAH, 2024)
Traumatic experiences make a person unhappy and often filled with excessive fear. For this reason, traumatic counseling services are needed to eliminate the symptoms of trauma experienced by the counselee. Ego state therapy is a short therapy technique based on the premise that personality consists of separate parts. Ego state therapy can effectively treat cases of trauma and excessive fear. The method used in this research is a qualitative method with literature study, namely a series of activities relating to library data collection methods, reading, recording and processing research materials. The data that has been collected is then analyzed using descriptive analysis methods. This article aims to find out the integration of ego state therapy. The final result of this research is to discuss: (1) ego state theory, (2) traumatic counseling, (3) ego state therapy techniques.